Current and Future Developments in Heritage Studies: From “Retrotopia” to “Prospective” - Fournier , Laurent Sébastien (Traditiones, 2021)
In the article, the author starts from the different approaches between heritage studies on the one hand and disciplinary heritage approaches on the other hand to consider current and future developments in the field of intangible cultural heritage. In the play between critical studies and broader studies, there are risks of regression as well as opportunities for progress. To underpin his analysis, he refers to his experience of development processes in the field of cultural heritage and to some recent research in France on the institutional functioning of UNESCO in the field of intangible cultural heritage. He then focuses on the notions of “retrotopia” (Bauman, 2017) and “prospective” (Godet, 2004), which seem to him to be suitable for triggering a fundamental anthropological reflection on the future of cultural heritage research. At the end, he draws some conclusions about the possibilities of progress – or, conversely, regression – in intangible cultural heritage.